Public Appeals and Collective Crisis Mitigation - Peter Haan; Lea Heursen; Jule Specht; Bruno Veltri; Georg Weizsäcker (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Arrivals of crises often trigger public appeals by policy leaders, attempting to motivate crisis-mitigating behaviors. We run a controlled experiment among a general-population sample to investigate the impact of such appeals and of their tonality. Varying the language, an identical content of the appeal – a plea to contribute to mitigating a crisis – is formulated with either positive or negative wordings. Relative to the case with no appeal, both types of appeals successfully raise contributions, each by about 20 percent. A separate sample of policy-makers is presented with our design and asked to estimate the effect of the appeals. They correctly predict the effect of the positively worded appeal but fail to predict the effect of the negatively worded one.
Keywords: 330